2010
DOI: 10.1186/1471-2334-10-351
|View full text |Cite
|
Sign up to set email alerts
|

Fusidic acid and clindamycin resistance in community-associated, methicillin-resistant Staphylococcus aureus infections in children of Central Greece

Abstract: IntroductionIn Greece, fusidic acid and clindamycin are commonly used for the empiric therapy of suspected staphylococcal infections.MethodsThe medical records of children examined at the outpatient clinics or admitted to the pediatric wards of the University General Hospital of Larissa, Central Greece, with community-associated staphylococcal infections from January 2003 to December 2009 were reviewed.ResultsOf 309 children (0-14 years old), 21 (6.8%) had invasive infections and 288 (93.2%) skin and soft tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…65 years. 1 Data from Central and Eastern European countries (2009) showed an average patient fatality rate of 19.1% for all adults aged $ 50 years, 10 again with incidence, mortality, and risk of hospitalization associated with increased patient age. A prospective study of patients with CAP, aged $ 65 years, found all-cause mortality within 1 year of hospital discharge to be 32.0% in a Hong Kong hospital from 2009 to 2010.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…65 years. 1 Data from Central and Eastern European countries (2009) showed an average patient fatality rate of 19.1% for all adults aged $ 50 years, 10 again with incidence, mortality, and risk of hospitalization associated with increased patient age. A prospective study of patients with CAP, aged $ 65 years, found all-cause mortality within 1 year of hospital discharge to be 32.0% in a Hong Kong hospital from 2009 to 2010.…”
Section: Introductionmentioning
confidence: 97%
“…A review of medical records in 309 children with communityassociated staphylococcal infections in Greece 19 demonstrated that there was a significant increase in MDR communityassociated methicillin-resistant Staphylococcus aureus (CA-MRSA), from 0% in 2003, to 31.2% in 2009 (P = 0.011). 19 In a prospective cohort study of 718 hospitalized patients from the community in Portugal, 20 organisms were isolated in a modest proportion of patients with CAP (13%) in Korea in 2008. 22 These data suggest that each patient should be assessed for risk factors for acquiring an MDR bacterial infection to determine the best approach to prevention and/or treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Countries that have used fusidic acid for some time have varied resistance problems. Resistance rates ranged from 1.4% for S. aureus in Sweden (260) to 89% in community-acquired MRSA in Greece (116); in Canada, where fusidic acid is also approved, resistance in S. aureus was 7.0% in the 2007-2008 time period, during which time only 0.3% of S. aureus isolates in the United States were fusidic acid resistant (117). Because of concerns about resistance, it has been suggested that fusidic acid should be dosed in combination with another orally active anti-MRSA drug such as rifampin.…”
Section: Fusidic Acidmentioning
confidence: 99%
“…In contrast to other CA-MRSA clones, the ST80 clone commonly carries the fusB gene, which appears to confer reduced susceptibility to FA. Studies from Greece and Kuwait have reported a high incidence of ST80 among CA-MRSA isolates and high rates of FA resistance [46,47]. According to recent data gathered by the Asian Network for Surveillance of Resistant Pathogens (ANSORP), which is a prospective, multinational surveillance study, ST80 has not been isolated in any Asian country [48].…”
Section: Fusidic Acid Resistance In Asiamentioning
confidence: 98%